UJI TINGKAT KEMATANGAN KOMPOS TERHADAP PRODUKSI TIGA VARIETAS BAWANG MERAH (Allium ascolanicumL) PADA TANAH GAMBUT - SELVIA SUTRIANA; RAISA BAHARUDDIN (Jurnal Ilmiah Pertanian, 2019)
ABSTRACT Low fertility was the problem of shallot development in peat.Compost with the right level of maturity can improve the characteristic of peat. Aim of this research was to determine the effect of maturity level of compostto production of three shallot varieties in peat. The experiment was conducted at Experimental Farm,Islamic University of Riau from April to August 2017. The research used a completely randomized design with 3 replications. Treatments were no compost, maturity level 1 week, 3 weeks, and 5 weeks and Kampar, Medan, and Brebes varieties. Compost of 3 week gave the best result on compost and peat soil analysis. However, Compost of1 weekprovides the highest increase on pH. Compostof 1 week significantly increase the number of bulbon Kampar variety ie 7.56 bulbs, while wet weight bulb and dry weight bulb per plot on Brebes varietyie 1062.83 g and 920.83 g.